Kajian Inferensi Wacana dalam Al-Qur'an - Patmalia, Nia (Mahira: Journal of Arabic Studies, 2022)
This study aims to identify, and describe; (1) types of discourse inference in the Qur'an, (2) the meaning of inference in the Qur'an. This research is a descriptive research that analyzes the discourse in the Qur'an. The results showed that the types of discourse inference contained in the Qur'an, including: political, social, economic, cultural, military, law and crime inference, sports, and education. And the meaning of inference contained in the Qur'an, including: prohibitions, promises of Allah, advice, orders, requests, threats, warnings, punishments, prohibitions against adultery, Allah is the Creator, and reading and writing is the key to knowledge.